Analisis Mobilitas Mayarakat Nomaden di Kepulauan Riau: Studi Orang Suku Laut Desa Berakit Kabupaten Bintan - Suryaningsih, Suryaningsih; Samnuzulsari, Tri; Arieta, Siti; Kurmalasari, Tety (Jayapangus Press, 2023)
The sea tribe people are one of the unique community groups that can be found in the Riau Islands. Currently, there are several sea tribe community groups that have begun to be placed in residential areas in regions in the Riau Islands. The uniqueness of the culture, traditions and lifestyle of the Sea Tribe people should be something that can be passed on to their future generations. As the lifestyle of the sea tribe people in Berakit Village has shifted to settling on land, their traditions, culture and customs are slowly disappearing. One of the distinctive features of the Sea Tribe people is wandering on a raft combing the islands along the Riau Islands coast. This study aims to highlight the mobility pattern of the Sea Tribe people in Berakit Village, Bintan Regency. Hence, this study was conducted on the sea tribe people to identify the mobility patterns that occur in Berakit Village, Bintan Regency. The purpose of this study is to understand the mobility pattern of the sea tribe in Berakit Village and the factors that influence it. The study method uses Qualitative Type. The results of the study indicate that the mobility pattern of the sea tribe in Berakit Village is influenced by various factors such as economy, social, politics, psychology, and place utility which means living on a raft on the sea has spiritual functions and values for them. This study also shows that the sea tribe's mobility is not entirely influenced by pressure or needs, but more on their cultural values and traditions. The study recommends that the local government needs to empower the sea tribe in cultural preservation and improving their quality of life. However, this intervention should be done by respecting and considering the cultural values of the sea tribe.